”Jeg er købmand og ikke filosof”: Sex, handel og venskab mellem kristne og muslimer i Boccaccios Decameron - Lausten, Pia Schwarz (K&K - Kultur og Klasse, 2017)
This article investigates the function of trade in the representation of Muslims and Islamic culture in Giovanni Boccaccio’s Decameron (1348-52). It is argued that trade establishes friendly contacts across religious and cultural differences, that the image of Muslims is less condemning than is case of Boccaccio’s contemporaries Dante and Petrarch, and that the Oriental world is represented as a place in which the Christians become rich and successful. Sometimes the Muslim world is indirectly represented as a place from which a critical view of Europe can be thrown. The article analyses two stories in particular: the second day’s seventh story about Saracen princess Alatiel who, despite having had sex ten thousand times with eight lovers, successfully presents herself to the King of the Algarve as his virgin bride, and the seventh day’s ninth story about Zinevra who escapes from her revengeful husband and travels to Aleksandria disguised as a male merchant. In different ways the stories merge sexual and trade logic. Boccaccio’s stories are not considered as realistic sources to get knowledge about the medieval world, but the article argues that geographical references to medieval trade centres and routes show that the stories are influenced by the merchant culture thematically and structurally.